SEROEPlDEMIOLOGY OF HELICOBACTER PYLORl - A. ÖZDEN; Ş. DUMLU; Ö. DÖNDERİCİ and H. ÇETİNKAYA and K. SOYLU and H. ÖZKAN and M. BALCI and M. SARIOĞLU and Ö. UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-